IP core protection and hardware-assisted security for consumer electronics - Sengupta, Anirban; Mohanty, Saraju P. (Materials, circuits and devices series, 2019)
The book addresses the general issue of protecting hardware (especially DSP cores) of consumer electronics (CE) as well as data on CE, including new demands created by IoT enabled products. It also addresses the potential threats from intervention in the CE design supply chain and how these threats can be circumvented. These supply chain security solutions may include hardware watermarking, hardware fingerprinting, symmetrical IP core protection, hardware metering, computational forensic engineering for IP core protection, and various forms of hardware obfuscation. It explores and addresses many different types of security attacks that can be launched against CE products, including power and timing "side channel" attacks, as well as backdoor and brute-force attacks. Methods are discussed for defeating/blocking Trojan horse attacks as well as reverse engineering attacks. The book discusses the latest methods for active and passive IP core security of DSP cores used in CE device and protection mechanisms for the buyers of ICs and incorporated IP that includes "watermarking"and "fingerprinting"as well as structural obfuscation, functional obfuscation, hardware AES, watermarked AES, and physically unclonable functions (PUFs). It also explores the use of forensic engineering for resolving ownership issues for reusable digital signal processing (DSP) IP cores. In addition to these direct security concerns, it discusses the trade-offs of energy consumption, security and performance for CE hardware